The Role Of Motivation In Mediating Culture Work And The Work Concept Of Work From Home (Wfh) On Employee Performance Post Pandemic Covid- 19 At Pt Tasblock Industry Indonesia - Sustenance Ananda Lubis , Fazar; Syaifuddin, Syaifuddin (Publisher Cv. Inara, 2022)
Work culture is something, a habit that is carried out in an activity that is impossible to change quickly a set of behaviors, feelings and psychological frameworks that are deeply internalized and shared by members of the organization ”. Osborn and Plastrik (2002:252 ) A person who feels his life satisfaction is fulfilled, then carrying out his work he enjoys his experiences which are accompanied by the level of joy Alston & Dudley (in Hurlock, 1980), where life satisfaction has brought an employee to work with high awareness and motivation for their duties and responsibilities. This research was conducted to prove the most appropriate model in influencing employee performance through motivation, Work from Home (WFH) Culture work Research approach using Structural Equation Modeling (SEM). of the 117 population of employees and taken 54 using the PT. Indonesian Industrial Tasblock. . Collecting data using a questionnaire is a way for researchers to obtain research data. Results This study shows that the Work and Work From Home curriculum directly has a significant effect on Employee Performance and the Work and Work From Home curriculum affects Employee Performance. Finally, indirectly, motivation has a significant effect in mediating the Curtur of Work and Work From Home on Employee Performance.